Efektivitas Penggunaan Media Smart Board dan Wordwall terhadap Minat Belajar Pendidikan Pancasila Siswa Sekolah Dasar - Aini, Fitria Nur; Nutria, Diah Ayu; Widodo, Silvirius; Widodo, Susilo Tri; Wahyuni, Nur Indah (Indonesian Journal of Education and Development Research, 2025)
The purpose of this study is to determine how well interactive learning tools, including Wordwall and the Smart Board, affect class IV A students' motivation in studying at SD Negeri Pendrikan Lor 02 in Pancasila Education. The Classroom Action Research (PTK) approach, which is conducted in two cycles, is used in this study. According to the study's findings, using interactive media greatly improves learning outcomes and student interest. The completion rate rose to 85.18% in cycle I and 100% in cycle II. In terms of making learning more dynamic and engaging and encouraging students to actively participate, the use of Wordwall and Smart Board has not only been successful but exceptional. These results have practical ramifications for using technology-based media to enhance learning, particularly in primary school Pancasila education. To ensure that these medium may continue to be used and to inspire educators and policymakers about the possibilities of these tools, it is advised that further training be given to instructors and that sufficient infrastructure be made available.